Importância prognóstica da proteína p53 nos pacientes tratados cirurgicamente com câncer de laringe - Enck Neto, Aloysio (2020)
More current studies on the molecular biology of laryngeal cancer seek to assess the correlation between the positivity of molecular markers to the aggressiveness and tumor recurrence of this disease. In order to analyze the expression of the p53 marker in patients treated surgically with laryngeal cancer, we sought to find a relationship between protein expression and laryngeal cancer prognosis. In this study we will address the expression immunohistochemistry of p53 in surgical pieces with free margins of patients with laryngeal cancer who underwent surgery between January 2014 and January 2018 at Hospital Universitário de Santa Maria (Husm) by the Head and Neck Surgery Service team. The positivity and expressiveness of the p53 marker were investigated in the samples and correlated with predisposing conditions (alcoholism and smoking), anatomical location, classification (TNM), presence of metastatic lymph node, recurrence, and survival. 39 surgically treated patients were analyzed, of which 53.8% had expression of the p53 marker. There was a significant difference in survival of patients with a positive p53 marker compared to those with a negative p53 marker (p = 0.039). Therefore, the p53 marker is also closely related to the recurrence of laryngeal cancer when associated with other factors, but when linked to smoking and the overexpression of the p53 protein, both are risk factors that, together, increase the chance of recurrence of the laryngeal tumor. Given the above, the importance of the p53 marker as an important ally in postoperative follow-up is confirmed.